Molecular marker learning modules: Vols 1 and 2 - Vicente, M. Carmen de; López, C.; Fulton, T.; Bioversity International (2004)
Volume 1: Using Molecular Marker Technology in Studies on Plant Genetic Diversity: Learning module Volume 2: Genetic Diversity Analysis with Molecular Marker Data: Learning Module Spanish version: Vol. 1 y 2 French version: Vol.1 et 2 Russian version: Vol.1 Russian version: Vol.2 These modules, developed jointly by Bioversity International and the Institute for Genomic Diversity, Cornell University, aim to promote capacity building and research biodiversity use and conservation worldwide through the application of molecular markers.They are especially directed to those countries with limited access to up-to-date scientific literature and research technologies. They discuss the fundamental principles of genetic diversity, the qualities of the markers used to measure it and the most widely used technologies, including those based on proteins, DNA and the polymerase chain reaction.These modules are intended for scientists with a minimal background in genetics and plant molecular biology, but with a working knowledge of plant genetic resources and issues concerning their conservation and management.